PEMBUATAN PROTOTYPE SISTEM E-LAPORAN BERBASIS WEB SEBAGAI PENDUKUNG PROGRAM SATU DATA PADA DINAS PU BINA MARGA DAN TATA RUANG PROVINSI SUMATERA SELATAN - Muhammad Kiki Nugraha; Diana Diana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The Department of Public Works for Highways and Spatial Planning (DPUBMTR) of South Sumatra Province is responsible for providing accurate infrastructure feasibility data, in line with Presidential Regulation No. 39 of 2019 on One Data Indonesia. In practice, the existing E-Laporan platform suffered from recurring bugs, a static interface, and insufficient server performance during peak usage. This study aims to redesign (rewrite) a web-based E-Laporan prototype to operate reliably on a local server (localhost). The development method used was the Prototyping model, covering requirements analysis, UI/UX design (Figma), back-end development using Native PHP, MySQL database management, and Bootstrap-based interface styling, followed by functional testing. Black Box Testing results confirmed that all core features—including authentication, CRUD operations, form validation, and dashboard charts—functioned correctly. Two technical issues were resolved during development: a MySQL port conflict (3306 redirected to 3307) and data type precision errors in road length calculations (INT changed to FLOAT). The resulting prototype successfully eliminated data duplication and accelerated the digitalization of physical records. Future development is recommended to deploy the system to a public cloud server.